Cardiovascular risk in Mozambique: who should be treated for hypertension? - Damasceno, Albertino (2013)
Aim: To estimate the proportion of Mozambicans eligible for pharmacological treatment for hypertension, according to single risk factor and total cardiovascular risk approaches. Methods: A representative sample of Mozambicans aged 40-64 years (n¼1116) was evaluated according to the WHO STEPwise Approach to Chronic Disease Risk Factor Surveillance (STEPS). We measured blood pressure (BP) and 12-h fasting blood glucose levels and collected data on sociodemographic characteristics, smoking, and use of antidiabetic and antihypertensive drugs. We estimated the 10-year risk of a fatal or nonfatal major cardiovascular event (WHO/International Society of Hypertension risk prediction charts), and computed the proportion of untreated participants eligible for pharmacological treatment for hypertension, according to BP values alone and accounting also for the total cardiovascular risk (WHO guidelines for assessment and management of cardiovascular diseases). Results: Among the Mozambicans aged 40-64 years and not taking antihypertensive drugs, less than 4% were classified as having cardiovascular risk at least 20% whereas the prevalence of SBP/DBP at least 140/90mmHg was nearly 40%. A total of 19.8% of 40-64-year-olds would be eligible for pharmacological treatment of hypertension according to the WHO guidelines, all of whom had SBP/DBP at least 160/100mmHg. Conclusion: Among the Mozambicans aged 40-64 years not taking antihypertensive drugs and having SBP/DBP at least 140/90 mmHg, only half were eligible for pharmacological treatment according to the WHO guidelines. Taking the latter into account, when defining strategies to control hypertension at a population level, may allow a more efficient use of the scarce resources available in developing settings. Keywords: diabetes mellitus, hypertension, Mozambique, risk assessment, smoking Abbreviations: BP, blood pressure; FBG, fasting blood glucose; ISH, International Society of Hypertension; STEPS, STEPwise Approach to Chronic Disease Risk Factor Surveillance; USD, United States Dollar